VALUASI EKONOMI KAWASAN WISATA PULAU PISANG KABUPATEN PESISIR BARAT - Arifa, Efti; Abidin, Zainal; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The objectives of this research are to analyze the travel cost of tourists of Pulau Pisang tourism area, factors that affecting the frequency of Pulau Pisang tourism area, and the economic value of Pulau Pisang tourism area. The research method used in this study is survey method involving 77 respondents. The study employs travel cost method. The research location is chosen purposively in Pulau Pisang of Pesisir Barat Regency. The data collection was carried out on February 2019. The travel expenses of visitors to Pulau Pisang tourism area was Rp341,563.39 per person in which the highest allocation of travel costs for transportation was Rp149,150.28 or 42% of the total cost of the trip. The factors affecting the frequency of visiting Pulau Pisang tourist areas were distance, age and travel cost. The economic value of Pulau Pisang travel cost in Pulau Pisang tourist areaswas Rp80,503,202,900,000.00 per year. Key words : economic value, tourist, travel cost